(untitled) (Research, Society and Development, 2021)
Currently, the choice of an adequate restoration of endodontically treated teeth is guided in part by the aesthetic requirement. Intraradicular pins are used when the dental remnant does not have adequate support for retention. In view of the difficulties in removing the fiberglass pins. The objective of this work, in vitro, was to compare two techniques of fiberglass pin wear to unclog root canals. Materials and Methods: the time to remove the fiberglass pin was evaluated. 26 standard single-toothed teeth were selected in 15 mm real working length (CRT). The chemical-mechanical preparation was carried out with the universal Protaper system. After filling, 10 mm of the canal was cleared, leaving 5 mm of material remaining in the apical third. The pins were cemented according to the manufacturer’s guidelines. The teeth were divided into two groups for the removal of the pin: In Group 01 (G1), the wear of up to 7 mm of the pin was performed using a multilaminated spherical drill No. 1 (LN), in low rotation, associated with the ultrasonic insert - conical TRI 01 DA3, under refrigeration, to wear the remaining pin. In Group 02 (G2) the wear of the pin was made using the PERIOSUB smooth trunk-conical ultrasonic insert, under refrigeration. Timing was performed during the removal of the fiberglass pin, where G1 obtained an average of 290 seconds and G2 with an average of 753 seconds, which was statistically significant (unpaired t test p ˂ 0.05). The G1 group had a shorter time for removing the fiberglass pin when compared to G2. The best option for removing the fiberglass pin seems to be the association of the spherical drill followed by the ultrasonic insert in the removal of fiberglass pins.